San Marino : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews economic developments in San Marino during 1990-94. The country came through the 1992-93 European recession virtually unscathed and took full advantage of the following recovery. Like surrounding areas of Italy, Sammarinese manufacturing and tourism sectors benefited from the depreciation of the lira after September 1992. In addition, the financial sector boomed as political turmoil in Italy caused large capital inflows. In this environment, the unemployment rate-already well below the European average-dropped to 3.8 percent in December 1995.